To build or buy? : the asset growth effect on organic and inorganic growth. - Chow, Jerome Ken Wen. (2012)
How will companies benefit from organic growth versus undertaking merger and acquisitions? This question is largely unanswered in the organizational growth literature. This paper studied the effect of undertaking both approaches on the stock performance of US firms. We tested for firm-level asset investment effects in returns by examining cross-sectional relations between an interaction variable, Merger Dummy x Asset Growth, and subsequent stock returns. We found that inorganic growth will result in lower stock returns as compared to organic growth. The implication of this study on the ‘build or buy’ decision suggests that an organic approach will result in less severe short-term negative returns relative to an acquisition.